Hepatocellular Carcinoma With Different Areas of Right Retroperitoneal Space Invasion: Evaluation of Transcatheter Arterial Chemoembolization Efficacy and Blood Supply Characteristics - Liu, Xi; Liao, Guangsheng; Luo, Xiaoping; Song, Wenlong; Zhang, Haiping; Chen, Hao; Cai, Shangzhi; Guo, Dajing (Frontiers in Oncology, 2020)
Purpose To evaluate the therapeutic efficacy of transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) with different areas of right retroperitoneal space (rRPS) invasion and analyze the blood supply. Methods This retrospective study enrolled 41 patients with HCC with different areas of rRPS invasion treated with TACE, including 22 HCCs with superior aspect of the right perirenal space (SARPS) invasion and 19 HCCs with right anterior pararenal space (RAPS) invasion. The overall response rate (ORR) and disease control rate (DCR) were analyzed. The prognostic factors for overall survival (OS) after TACE were determined. The blood supply characteristics of HCC with different areas of rRPS invasion were analyzed with arteriograms. Results All patients underwent 2.8 ± 1.8 TACE sessions over 25.0 ± 21.9 months. The median OS was 29.0 months for patients with SARPS invasion and 12.0 months for patients with RAPS invasion (P = 0.004). Only the invaded area of the rRPS was an independent prognostic factor for OS [hazard ratio (HR), 2.833; 95% CI, 1.297–6.188; and P = 0.009). The ORR and DCR were significantly higher in the group with SARPS invasion than in the group with RAPS invasion (ORR: 63.6% vs 31.6%, P = 0.041; DCR: 77.3% vs 47.4%, P = 0.047). Initially, HCC with SARPS invasion were supplied by the hepatic artery (HA; n = 8) and both the HA and extrahepatic collateral vessels (EHCs; n = 14); HCC with RAPS invasion were supplied by the HA (n = 10) and both the HA and EHCs (n = 9); as the TACE sessions increased, the tumor-feeding vessels shifted from the HA to both the HA and EHCs, and even EHCs could be the only blood supply. Rare EHCs appeared earlier and more frequently in the RAPS group than in the SARPS group. Conclusion The efficacy of TACE differed for HCC with different areas of rRPS invasion, and the median OS, ORR and DCR were significantly better in the SARPS group than in the RAPS group. Different common EHCs supplied HCCs with different areas of rRPS invasion, while other rare EHCs appeared more frequently in the RAPS group.